UK response to new trade Union strategies for new forms of employment. Issue 3 (September 2019) - Freedland, Mark; Dhorajiwala, Hitesh
This paper records the responses to the questionnaire that was circulated to academics for the purposes of compiling the ETUC publication, 'New trade union strategies for new forms of employment'. In responding to the questions asked, this paper provides a broad description of how work relationships are organised in English law, including the various tests and criteria that are relevant to particular work relationship statuses which determine access to both individual and collective employment rights. This also involves discussing the relationship between newer intermediate work relationship statuses, and the traditional binary divide upon which English employment law is premised. The paper finally turns to assessing hypothetical scenarios against the tests for work relationship status in English law, as well as possible reform proposals that could help to increase coverage for workers.